Role, management, and outcome of free flap reconstruction for acute full-thickness burns in hands - Ziegler, Benjamin; Bickert, Berthold; Kneser, Ulrich; Hirche, Christoph (Annals of plastic surgery, 2020)
Introduction - Severe thermal trauma to the hand can result in major impairment and reduced function due to defective healing or even extremity loss. Full-thickness injuries frequently incur exposure of tendons or bone and require an early and stable coverage with soft tissue transplants to allow for rapid induction of exercise and to preserve structures and hand function. Free tissue transfer to the hand after thermal trauma is a rare indication, and safety, management, and outcome of free flap surgery for severe acute burn injuries to the hand remains underreported. - Methods - Patients with primary reconstructions of full-thickness burn injuries to the hand undergoing microsurgical free tissue transfer surgery were retrospectively assessed in a period from 2013 to 2016. Salvage strategy of the extremity, postoperative complications, length of hospital stay, and primary reconstructive result were quantified and analyzed. Functional outcome measures (range of motion and grip strength) were assessed during clinical follow-up examinations. - Results - During the investigated period, 13 patients were identified undergoing reconstruction of 14 hands via free flap transplantation after severe burn injury in the acute phase. Nine anteriolateral thigh flaps (64%), 3 latissimus dorsi flaps (18%), 1 serratus anterior flap, and 1 tensor fasciae lata flap (7%) were performed. In all cases, salvage of the affected extremity was achieved, although 1 flap (7%) was lost during the early postoperative period requiring secondary reconstruction via pedicled groin flap. Further complications were venous thrombosis (n = 2; 14%) and hematoma (n = 2; 14%). Mean length of hospital stay was 51 days. Functional outcome during follow-up examination after an average of 9.3 months was inhomogeneous depending on the pattern of injury and ranged from complete recovery to nearly entire loss of hand function. - Conclusions - Free flap transfer can be a mandatory and valuable tool to cover full-thickness burn injuries of the hand early in the clinical course of thermal trauma and may provide extremity salvage by favorable means of reconstruction to achieve acceptable functional outcomes, in the most severe cases. Although microsurgical failure rates in burn patients are slightly higher than in free flap transfer to the upper extremity in general, it can be performed with reasonable risk-to-benefit ratio.
Gesehen am 16.09.2020